2014
DOI: 10.1152/japplphysiol.01251.2013
|View full text |Cite
|
Sign up to set email alerts
|

Peak exercise oxygen uptake during and following long-duration spaceflight

Abstract: This investigation was designed to measure aerobic capacity (V̇o2peak) during and after long-duration International Space Station (ISS) missions. Astronauts (9 males, 5 females: 49 ± 5 yr, 77.2 ± 15.1 kg, 40.6 ± 6.4 ml·kg(-1)·min(-1) [mean ± SD]) performed peak cycle tests ∼90 days before flight, 15 days after launch, every ∼30 days in-flight, and on recovery days 1 (R + 1), R + 10, and R + 30. Expired metabolic gas fractions, ventilation, and heart rate (HR) were measured. Data were analyzed using mixed-model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 38 publications
4
63
1
1
Order By: Relevance
“…We confirmed here that astronauts perform aerobic exercises for only about 30 min/day within a lifestyle that has greatly reduced overall daily activity compared with preflight (9). Reduced activity can affect maximum oxygen uptake (29), skeletal muscle function, and bone loss (43,52). In this study, the concern is that the relatively sedentary lifestyle of an astronaut can be compared with the modern epidemic of sedentary behavior associated with high incidence of cardiometabolic disease (4,35).…”
Section: Discussionsupporting
confidence: 66%
“…We confirmed here that astronauts perform aerobic exercises for only about 30 min/day within a lifestyle that has greatly reduced overall daily activity compared with preflight (9). Reduced activity can affect maximum oxygen uptake (29), skeletal muscle function, and bone loss (43,52). In this study, the concern is that the relatively sedentary lifestyle of an astronaut can be compared with the modern epidemic of sedentary behavior associated with high incidence of cardiometabolic disease (4,35).…”
Section: Discussionsupporting
confidence: 66%
“…Data from the ISS have recently indicated that astronauts only lose a few kilogrammes of body mass during months of flight (Zwart et al 2014) and this cannot explain the decrease in blood pressure of 8-10 mmHg. The exercise countermeasures (Wood et al 2011;Smith et al 2012) on the ISS probably also did not account for our observations by themselves because (i) 24 h heart rate and blood concentration of noradrenaline should then have been lower (Leosco et al 2013); (ii) aerobic exercise for several months in normotensive individuals of the same age as our astronauts does not decrease blood pressure (Mortensen et al 2014); and (iii) aerobic capacity is decreased by 17% in astronauts on the ISS despite the use of exercise countermeasures (Moore et al 2014). Thus, a lower aerobic fitness cannot contribute to decreased systemic vascular resistance and blood pressure.…”
Section: Systemic Vascular Resistancementioning
confidence: 80%
“…); and (iii) aerobic capacity is decreased by 17% in astronauts on the ISS despite the use of exercise countermeasures (Moore et al . ). Thus, a lower aerobic fitness cannot contribute to decreased systemic vascular resistance and blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Recent upgrades to the resistive (Loehr et al., 2011) and treadmill exercise capabilities, coupled with enhanced nutritional practices, have resulted in improved health outcomes (Smith et al., 2012). Currently, ISS astronauts are scheduled for up to 2.5 h day −1 for exercise preparation, execution and clean‐up, which typically includes ∼30 min of aerobic exercise (choice of treadmill or cycle) and ∼45 min of resistive exercise (Moore et al., 2014). The ISS exercise prescriptions are based on the demonstrated efficacy of countermeasures that combat musculoskeletal and cardiovascular deconditioning in bed rest models (Pavy‐Le Traon et al., 2007; Lee, Moore, Everett, Stenger, & Platts, 2010; Ploutz‐Snyder et al., 2014; Shackelford et al., 2004; Trappe, Burd, Louis, Lee, & Trappe, 2007), and include both continuous and interval aerobic exercise training and resistive exercises, focusing on the trunk and lower body, where the majority of the musculoskeletal losses occur (LeBlanc et al., 2000a,b).…”
Section: Discussionmentioning
confidence: 99%